Conversor para pulsos elétricos de alta tensão, de curta duração, para processos de geração de ozônio - Hincapie Baena, Alejandro [UNESP] (2014)
This research proposes, analyzes and implements a converter for generating high voltage electric pulses for application to ozone production and injection in water for the purpose of bactericidal and germicidal processes for cleaning and sanitizing industry applications. The proposed converter consists of two stages, the first stage being a Boost rectifier operating in Discontinuous Conduction Mode (DCM), responsible for getting a Continuous Current (CC) bus regulated and, acting as input voltage follower presents a high power factor with reduced harmonic distortion to the input current; the second stage involves the use of a resonant Full–Bridge inverter controlled by phase–shift, using constant frequency (close to 10kHz) and bipolar modulation. The resonant inverter stage is composed of the bridge inverter associated with a step–up transformer, inductors and capacitors to adjust de resonant frequency, resulting in a structure capable of generating electric pulses with amplitude at the output of almost 6kV, which are applied on a set of fourteen (14) discharge chambers in parallel for ozone generation and injection in water. The work presents a literature review for the applications of ozone, the main converter topologies at low power for generating electrical pulses in ozonizators, the analysis of a commercial product, a proposal and development of a power converter structure to replace the commercial one, resulting in better efficiency and high input power factor, presenting their qualitative and quantitative analysis, modeling, design methodologies, implementation of a functional prototype, the main experimental results and proposal of continuity of future researches